IMPROVING THE ACCURACY OF DETERMINING THE COORDINATES OF GROUND-BASED RADIOELECTRONIC MEANS IN SATELLITE RADIO MONITORING - Kulakayeva, A.; Daineko, Е.А.; Aitmagambetov, А.З.; Ongenbayeva, Ж.Ж.; Kozhakhmetova, Б.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
This article substantiates the possibility of increasing the accuracy of determining the coordinates of radio emission sources by repeatedly measuring the parameters of a ground-based radio emission source, where the bearings are determined at several (at least two) points of the orbit of a low-orbit small spacecraft. The proposed algorithm will make it possible to perform data processing with less time, therefore, it is more efficient than using the iteration method. It can also serve as a basis for evaluating and analyzing the parameters of radio emission source signals in a wide frequency range with the possibility of locating radio emission sources. The paper also presents a program for determining the latitude and longitude coordinates of a radio source by measuring at two different points in the orbit of a small spacecraft. This computer program is made in C#.